Managing HR for organizational performance - Sparrow, Paul (Henry Stewart Talks, 2011)
High performance work systems and bundles of practices, A dialogue with other disciplines (strategy, organization design, innovation, and customer service), 'Value' in the context of business model change, Performance logics associated with productivity, innovation and customer centricity, Building an organization design capability, Thinking about jobs-based flexibility, Tackling the challenge of engagement and performance belief